Antioxidant and anti-inflammatory activity of capitula, leaf and stem extracts of Tanacetum cilicicum (Boiss.) Grierson - DOĞAN, AHMET; ŞEN, ALİ; BİTİŞ, LEYLA (My University, 2019)
In this study, various extracts obtained different parts of Tanacetumcilicicum were investigated for in vitro antioxidant and anti-inflammatoryactivity. Antioxidant activity was tested with three methods; namely 2.2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging capacity, 2.2′‐azinobis (3‐ethylbenzothiazolin‐6‐sulphonic acid) (ABTS) radical cation scavengingcapacity, and ferric-reducing antioxidant power (FRAP) assays. Total phenolicand flavonoid contents of extracts were determined by Folin-Ciocalteu andaluminum chloride methods, respectively. Also, anti-inflammatory activity ofthese extracts was evaluated by 5-lipoxygenase inhibition assay. Ethyl acetateextract of capitula of T. cilicicum (TCCEA) showed the highest antioxidantactivity with IC50 values of 22.44 and 30.86 μg/mL against DPPH and ABTSradicals, respectively. At the same time, the highest ferric reducing power wasfound in the TCCEA (42.2 mg TE/g extract). The highest total phenolic contentshave been detected in TCCEA and ethyl acetate extract of leaves of T. cilicicum(TCLEA) with value of 174.1 and 175.6 mg GAE/g extract, respectively.Similarly, the highest total flavonoid contents have been detected in TCCEA andTCLEA with values of 26.94 and 30.48 mg QE/g extract, respectively. TCCEAexhibited strong anti-inflammatory activity with IC50 value of 9.44 μg/mL whencompared to standard indomethacine (22.39 μg/mL). These results demonstratethat TCCEA has a significant antioxidant and anti-inflammatory activity. Also,the results show that TCCEA is a good candidate for further bioactivity-guidedfractionation in the search for new active anti-inflammatory and antioxidantcompounds.
Keywords: Biyoloji